Perubahan Fungsi Lahan Pertanian Di Kawasan Wisata, Faktor Penyebab Dan Strategi Penanggulangannya - I Ketut Sumantra; Mohammad Dieng Mahardika; I Ketut Arnawa (Universitas Lambung Mangkurat, 2020)
Interpretation of the function of agricultural land that is unstoppable can threaten the availability of food, and in the long term can cause environmental, economic, and social losses. On the other hand, the effectiveness of the implementation of land use control instruments has not run optimally as expected. The village of Tibubeneng, North Kuta sub-district, Badung Regency was used as the object of research because the amount of agricultural land conversion was very high due to the development of tourism facilities. The research was aims to determine the change in land used for tourism activities and the factors that influence it and to find out the changes in land use and driving factors using observation and interview methods. Data on land-use change uses overlay techniques while to determine the driving factors for agricultural land change using the method Principal Component Analysis. The results showed that the biggest changes in land use for tourism activities occurred in rice fields, with a change of 40.52%. Economic factors and the availability of infrastructure are the dominant factors in changing the function of agricultural land for tourism activities. Reducing the conversion of agricultural land functions needs to be done: 1) integration of agricultural activities with the tourism sector. 2) Increase and strengthen the economic role of rural communities through the establishment of BUMDes. 3) Increase and optimize supervision and control of buildings that violate applicable regulations. 4) Designing spatial products related to controlling land-use utilization. 5) Implement a system of incentives and disincentives so that the economic interests of the population can be sustained.